2003
DOI: 10.1016/s0002-9270(03)01695-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of sertraline as a treatment for cholestatic pruritus in patients with primary biliary cirrhosis

Abstract: Sertraline use is associated with an improvement in cholestatic pruritus. This novel observation implies that serotonergic fibers are important in regulating the perception of itch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 0 publications
0
33
0
4
Order By: Relevance
“…In a retrospective review, the use of sertraline (75 mg per day), a serotonin re-uptake inhibitor, was reported to be associated with improvement of pruritus in a small group of patients with PBC, who had recorded the perception of pruritus in their personal diaries as part of their participation in a clinical trial [116]. Any relationship between the reported effect of sertraline on pruritus and on mood is unknown at present.…”
Section: Sertralinementioning
confidence: 99%
“…In a retrospective review, the use of sertraline (75 mg per day), a serotonin re-uptake inhibitor, was reported to be associated with improvement of pruritus in a small group of patients with PBC, who had recorded the perception of pruritus in their personal diaries as part of their participation in a clinical trial [116]. Any relationship between the reported effect of sertraline on pruritus and on mood is unknown at present.…”
Section: Sertralinementioning
confidence: 99%
“…Tab. 1, [21]). In einer Dosisfindungsstudie zur Therapie mit Sertralin bei 21 Patienten mit Lebererkrankungen wurde zunächst eine offene Anwendung durchgeführt [22].…”
Section: Pruritustherapie Mit Tetrazyklischen Antidepressivaunclassified
“…Nur wenige dieser Studien untersuchten die Beschwerdesymptomatik gezielt mithilfe von visuellen Analogskalen oder evalulierten Fragebögen [17,21,22,23]. Ferner wurde der Großteil der Studien nicht placebokontrolliert durchgeführt.…”
Section: Zusammenfassende Beurteilungunclassified
“…A trial of cholestyramine can be attempted although the drug should be administered several hours apart from other medications to prevent its interference with their absorption. Alternative agents that have been studied to treat pruritus include sertraline, a serotonin reuptake inhibitor that has been shown to moderately improve pruritus in cholestatic patients [29,30]. Other agents that have been studied include rifampicin and the opioid receptor antagonists naltrexone and naloxone [31].…”
Section: General Guidelinesmentioning
confidence: 99%